2008
DOI: 10.1080/00365590802028141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varicocelectomy on serum inhibin B levels in infertile patients with varicocele

Abstract: Serum inhibin B level as an endocrine marker combined with a spermogram could provide efficient data for evaluating the effect of varicocelectomy on spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Therefore, both PDRN and surgical treatment re-create a microenvironment where the Sertoli cells may normally function. In agreement with this hypothesis, it has been demonstrated (27,28) that varicocelectomy increases inhibin expression.…”
mentioning
confidence: 50%
“…Therefore, both PDRN and surgical treatment re-create a microenvironment where the Sertoli cells may normally function. In agreement with this hypothesis, it has been demonstrated (27,28) that varicocelectomy increases inhibin expression.…”
mentioning
confidence: 50%
“…In men with severe oligoasthenoteratozoospermia, treatment of varicocele was associated with a significant increase in inhibin B levels and a significant decrease in FSH levels [8]. Some researchers have noted a significant improvement in serum inhibin B level after varicocelectomy and have concluded that combining this endocrine marker with a spermogram could be an effective guide to the effect of varicocelectomy on spermatogenesis [12, 30]. In contrast, our present results confirmed those of Fujisawa et al [11], in which the preoperative serum inhibin B concentration did not reliably predict the response to varicocelectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to demonstrate a reverse correlation as testicular volume decreases in patients with varicocoele (Romeo et al, 2007). Because levels of inhibin B have also been found to increase or decrease non-specifically in some adolescents and adults, with or without surgical correction, there is poor evidence to support its clinical application (De Sanctis et al, 2007;Di Bisceglie et al, 2007;Ozden et al, 2008;Basar et al, 2010). For example, one analysis of variance study, between 50 men with varicocoele, 50 adolescents with varicocoele and 50 fertile adults without scrotal pathology, found no correlation of serum and seminal plasma inhibin-B levels between groups (Basar et al, 2010).…”
Section: Predictors Of Testicular Injury/indicators Of Surgerymentioning
confidence: 99%